1994
DOI: 10.1007/bf00993044
|View full text |Cite
|
Sign up to set email alerts
|

Competition-based induction of decision models from examples

Abstract: Abstract. Symbolic induction is a promising approach to constructing decision models by extracting regularities from a data set of examples. The predominant type of model is a classification rule (or set of rules) that maps a set of relevant environmental features into specific categories or values. Classifying loan risk based on borrower profiles, consumer choice from purchase data, or supply levels based on operating conditions are all examples of this type of model-building task. Although current inductive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(33 citation statements)
references
References 2 publications
0
31
0
2
Order By: Relevance
“…In this model the chromosomes compete and cooperate simultaneously. COGIN [49], REGAL [44] and LOGENPRO [106] are examples with this kind of representation.…”
Section: Genetic Learning: Rule Coding and Cooperation/ Competition Ementioning
confidence: 99%
“…In this model the chromosomes compete and cooperate simultaneously. COGIN [49], REGAL [44] and LOGENPRO [106] are examples with this kind of representation.…”
Section: Genetic Learning: Rule Coding and Cooperation/ Competition Ementioning
confidence: 99%
“…The basic concept of decision tree induction is based on a greedy algorithm that constructs a decision tree in a top-down, recursive, and divideand-conquer manner (Greene & Smith, 1993). The ID3 algorithm (Quinlan, 1986) is an iterative decision tree induction algorithm that generates simple trees with higher predictive accuracy instead of complex trees.…”
Section: Decision Tree Analysismentioning
confidence: 99%
“…In this model, the chromosomes compete and cooperate simultaneously. COGIN (Greene and Smith 1993), REGAL (Giordana and Neri 1995), G-Net (Giordana et al 1997), OCEC (Jiao et al 2006), EDGAR (Rodríguez et al 2010) and DOGMA (Hekanaho 1997) are examples that can be located in this framework.…”
Section: Genetic Learningmentioning
confidence: 99%
“…These are OCEC (Jiao et al 2006) and COGIN (Greene and Smith 1993) as GCCL methods. Due to CORE (Tan et al 2006b) has shown a low performance, we decided to replace it by GIL (Janikow 1993), which is a GBML algorithm that only works with nominal values, as in our proposal.…”
Section: Algorithms Considered For Comparisonmentioning
confidence: 99%